A Discourse Of Doctoral Qualifying Exam: A Self Observation And Reflection - Yazid Basthomi (Universitas Negeri Malang, 2016)
This study, concern itself with a discourse of doctoral qualifying exam, an underresearched area of doctoral studies in the Indonesian context, concerns itself with a discourse of doctoral qualifying exam. The data for this study were drawn from naturalistic observations taking place during the doctoral ventures of the present researcher. Another methodological characteristic of the present study is the employment of selective self-reflections on the personal narratives of the researcher. The researcher attended some ten doctoral qualifying exams at one graduate school of one of Indonesian universities. The study arrived at two conspicuous features characterizing doctoral qualifying exams. Results of some comparative observations taking place in Thailand, Australia, and the United Sates are also presented to help clarify the characterization of the doctoral qualifying exams in the Indonesian university. Some recommendations for future research concerning doctoral studies will conclude the article